Dynamics of Phosphorus and Biostimulants on Agro-Morphology, Yield, and Essential Oil Profile of German Chamomile (Matricaria chamomilla L.) Under Acidic Soil Conditions of the Western Himalaya - Rathore, Shalika; Kumar, Rakesh (Frontiers in Plant Science, 2022)
German chamomile (Matricaria chamomilla L.) is a promising and easy cultivating crop in suitable nutrient supply conditions, but acidic soils of Indian western Himalayas limit the phosphorus availability to plant and reduce flower production. Thus, a field experiment was conducted for two consecutive seasons (2018‒2019 and 2019‒2020) to study the effect of phosphorus dynamics and biostimulant application on agro-morphological traits, essential oil (EO) yield, and chemical constituents of German chamomile in the mid-hills of the western Himalayan region. The experiment consisted of twelve treatments; four phosphorus fertilizer levels (0, 30, 60 and 90kg ha-1) and three biostimulants levels (Control, amino acid at 5mL L-1 and humic acid at 10mL L-1). The experiment was replicated three times in a factorial complete randomized block design (FRBD). Agro-morphological and yield characteristics were significantly higher in phosphorus at 90kg ha-1 and humic acid application compared to control. The dry flower and EO yield was 17.87% and 26.76% higher with 90kg ha-1 phosphorus application while 2.45% and 5.79% higher in humic acid at 10mL L-1 compared to control. The EO constituents viz., chamazulene was 12.04% and 8.85% higher in phosphorus at 90kg ha-1 and humic acid at 10mL L-1 application compared to control. On the other hand, α-bisabolol oxide B and α-bisabolol oxide A decreased with an increase in phosphorus application. This study presents novel facts, elucidation, and explanation for farmers and industrialists to produce German chamomile in acidic soils by integrating biostimulants with in phosphorus fertilization and getting maximum yield and quality EO.